2021
DOI: 10.1093/clinchem/hvab192
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Plasma Biomarker Diagnostic Model Incorporating Ultrasensitive Digital Immunoassay as a Screening Strategy for Alzheimer Disease in a Chinese Population

Abstract: Background The ultrasensitive detection of blood-based biomarkers such as amyloid β (Aβ), tau, and neurofilament light (NFL) has drawn much attention in Alzheimer disease (AD) diagnosis. However, few studies have been conducted in the Chinese population. This study aimed to evaluate the ability of plasma biomarker diagnostic models for AD in the Chinese population based on a novel digital immunoassay technology. Methods 159 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 48 publications
5
42
0
Order By: Relevance
“…Other works, while not using a ratio, have also identified that combination analyses on p-tau, Aβ and clinical features can better distinguish AD from unimpaired populations [36] than analyses of analytes alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other works, while not using a ratio, have also identified that combination analyses on p-tau, Aβ and clinical features can better distinguish AD from unimpaired populations [36] than analyses of analytes alone.…”
Section: Discussionmentioning
confidence: 99%
“…The current work, conducted in in a larger cohort and in a different ethnic group, supports the utility of this measurement approach. Other works, while not using a ratio, have also identified that combination analyses on p-tau, Aβ and clinical features can better distinguish AD from unimpaired populations [36] than analyses of analytes alone.…”
Section: Discussionmentioning
confidence: 99%
“…This is tabulated in Table 1. Of the 28 studies analyzed over the 10-year period, 0 were from 2012, 3 from 2013, [18-20] 2 were from 2014, [21,22] 0 were from 2015, 1 was from 2016, [23] 2 were from 2017, [24,25] 5 were from 2018, [26-30] 3 were from 2019, [31][32][33] 3 were from 2020, [34][35][36] 7 were from 2021, [37][38][39][40][41][42][43] and 2 were from 2022. [44,45] All involved older adults, 61% were quasi-experimental, 21% were observational, and 14% were true experiments.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Blood based biomarkers were identi ed in 6/28 (21%) of the studies analyzed. [18,26,32,35,40,43] This intervention is more invasive than imaging and causes more risk. Various forms of telehealth were implemented to diagnose AD in 4/28 (14%) of the studies analyzed.…”
Section: Additional Analysis and Certainty Of Evidencementioning
confidence: 99%
“…12 This digital protein analysis significantly improves the detection sensitivity of target protein biomarkers to the level of attomole (aM), and it has great potential in disease diagnostics, including Alzheimer's disease, cancer, immune system disorders, and ischemic stroke. [13][14][15][16] Digital cell analysis can compartmentalize single cells in individual volumes, and it enables the investigation of the behaviour of single cells and cell heterogeneity. [17][18][19][20] These digital biological analysis methods can open up new frontiers for biological research and provide promising tools for disease diagnostics and monitoring.…”
Section: Introductionmentioning
confidence: 99%